Satisfying the Need for Relatedness Among Teachers: Benefits of Searching for Social Support - Maas, Jasper; Schoch, Simone; Scholz, Urte; Rackow, Pamela; Schüler, Julia; Wegner, Mirko; Keller, Roger (Frontiers in Education, 2022)
The satisfaction of teachers’ need for relatedness is an important pre-condition for teachers’ wellbeing. Receiving social support plays an important role in satisfying the need for relatedness. Following job crafting theory, the present study aims to examine (1) whether searching for social support results in an increase in the satisfaction of the need for relatedness and (2) whether this effect is mediated by an increase of received social support from the school principal and from colleagues. Using longitudinal data (N = 1071) we calculated residualized change scores and applied structural equation modeling to test the hypothesized mediation model. Results confirmed the beneficial effect of searching for social support on the satisfaction of the need for relatedness. This effect included a direct effect and an indirect effect through the receipt of social support from colleagues. The receipt of social support from the school principal was positively related to searching for social support but was unrelated to the satisfaction of the need for relatedness. These findings emphasize the importance that teachers build strong and supportive relationships within the school team, as this helps to satisfy their need for relatedness, which in turn contributes to better wellbeing among teachers.